A rare case of ectopic pregnancy: cornual pregnancy following salpingectomy - Jaafar, Wissal; Medemagh, Malek; Souilah, Selma; Mohamed, Chayma Cheikh; Fekih, Ichrak Ben; Godcha, Samar; Khalifa, Nahed; Mourali, Mechaal (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
The implantation of a fertilized egg outside the uterine cavity is known as an ectopic pregnancy, and usually occurs in the fallopian tubes. Few cases, have been reported where implantation has occurred in atypical sites. We report the case of an ectopic pregnancy that occurred in the residual stump after salpingectomy. It seems that a pregnancy implanted in this location is very uncommon, making correct diagnosis difficult. This paper includes a brief description of the case, a review of the different diagnostic and therapeutic methods available to this day, and a brief review of the literature.